Soft and Hard Skills of Software Testing Professionals: A Comprehensive Survey - Valle, Pedro Henrique Dias; Vilela, Ricardo Ferreira; Guerino, Guilherme; Silva, Williamson (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2023)
The development of skills and competencies required by computing professionals plays a crucial role in ensuring the quality of software products before their implementation. In particular, the software industry has increasingly sought professionals with management, communication, innovation, and social skills. There needs to be more comprehensive research in the literature that addresses both the technical skills (hard skills) and the behavioral skills (soft skills) required by software testing professionals. This paper presents the results of a survey conducted with 101 software testing professionals. The goal was to highlight information about the soft and hard skills that are important for professionals who work with software testing. In addition, we identified the tools and programming languages employed to support the activity testing software. The results of this work provide valuable insights into the most relevant technical and behavioral skills for testing professionals, which are required for them to perform their jobs efficiently and effectively.